Odon de Cluny: Vita sancti Geraldi Auriliacensis. Édition critique, traduction française, introduction et commentaires. Edited by A. M. Bultot-Verleysen - Ward, Benedicta (The journal of theological studies, 2010)
This latest volume from the Bollandists’ Subsidia hagiographica is a notable achievement. It is the first academic work to be done on the Latin text of Odo of Cluny’s De Vita Sancti Geraldi Aurilensis Comitis since the edition in PL 133, cols. 629–703. There have been at least three studies of Odo as second abbot of Cluny and much more has been written on his wide influence in church and state. There are several encyclopedia entries for both him and for Gerald but less has been written about Odo as a writer. Mme Bultot-Verleysen has presented a fine critical edition of Odo’s Latin text with a French translation of the books of Gerald’s life and miracles. There are 128 invaluable pages of introduction and notes, a map, and indexes.